2018
DOI: 10.18388/abp.2017_1588
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic signalling in B cells

Abstract: Adenosine and adenosine triphosphate are involved in purinergic signaling which plays an important role in control of the immune system. Much data have been obtained regarding impact of purinergic signaling on dendritic cells, macrophages, monocytes and T lymphocytes, however less attention has been paid to purinergic regulation of B cells. This review summarizes present knowledge on ATP- and Ado-dependent signaling in B lymphocytes. Human B cells have been shown to express A-AR, A-AR, A-AR and A-AR and each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 43 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…Due to their role in secreting antibodies and presenting antigens, B lymphocytes are the main actors in the humoral component of the adaptive immune system, and mature to plasma cells following the contact with specific antigens. The involvement of Ado signaling in the regulation of B lymphocyte functions has been well documented, starting from the demonstration that all four ARs are expressed by murine and human B cells, together with ecto-enzymes and membrane nucleoside transporters (for review see Reference [20]). In particular, it has been observed that inactivated B cells remain under the inhibitory effect of autocrine and paracrine Ado, whereas activated B cells increase ATP synthesis and release.…”
Section: Adaptive Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their role in secreting antibodies and presenting antigens, B lymphocytes are the main actors in the humoral component of the adaptive immune system, and mature to plasma cells following the contact with specific antigens. The involvement of Ado signaling in the regulation of B lymphocyte functions has been well documented, starting from the demonstration that all four ARs are expressed by murine and human B cells, together with ecto-enzymes and membrane nucleoside transporters (for review see Reference [20]). In particular, it has been observed that inactivated B cells remain under the inhibitory effect of autocrine and paracrine Ado, whereas activated B cells increase ATP synthesis and release.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…In particular, it has been observed that inactivated B cells remain under the inhibitory effect of autocrine and paracrine Ado, whereas activated B cells increase ATP synthesis and release. ATP in turn protects B cells from Ado-induced inhibition, exerts a pro-inflammatory effect on the target tissues, and stimulates IgM release [20]. On the other hand, studies on rodents showed that Ado synthesis is necessary for the development, implantation and maintenance of the plasma cell population in the bone marrow during the primary immune response.…”
Section: Adaptive Immunitymentioning
confidence: 99%
“…Purinergic signaling system is a revolutionary selected system that can finetune the function of immune cells (1). In fact, purinergic signals mediated by P2R and P1R often play the opposite role in regulating the function of immune cells (9). Specifically, ATPmediated P2 receptor signal generally promotes the activation of immune cells, while ADOmediated P1R signal mainly limits the activation of immune cells (2,10).…”
Section: Introductionmentioning
confidence: 99%
“…Gs/Gi protein activation, however, will work through the stimulation/inhibition of adenylate cyclase, respectively, with subsequent up- or down-regulation of cyclic AMP (cAMP) production. Final effects of purinergic receptor-promoted signaling will depend on the cell type and other intra-/inter-cellular conditions, as i.e., in physiological embryonic and adult neurogenesis (Oliveira et al, 2016 ), and in various pathological scenarios, such as inflammatory (Beamer et al, 2016 ; Madeira et al, 2017 ; Przybyła et al, 2018 ), oncological (Allard et al, 2016 ; Vijayan et al, 2017 ; Whiteside, 2017 ; Kazemi et al, 2018 ), neurological (Burnstock et al, 2011 ; Stockwell et al, 2017 ), metabolic (Lindberg et al, 2015 ; Csóka et al, 2017 ; Parpura et al, 2017 ; Tozzi and Novak, 2017 ; Labazi et al, 2018 ), psychiatric (Cunha, 2008 ; Lindberg et al, 2015 ; Ortiz et al, 2015 ; Krügel, 2016 ; Cheffer et al, 2017 ; Oliveros et al, 2017 ), cognitive (Illes and Verkhratsky, 2016 ), and peripheral neuromuscular and/or neuromotor diseases (Robitaille, 1995 ; Kalmar, 2005 ; Burnstock et al, 2013 ; Jiménez et al, 2014 ; Bogacheva and Balezina, 2015 ; Puchałowicz et al, 2015 ; Safarzadeh et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%